Turkey : Second Review Under the Stand-By Arrangement-Staff Report; Staff Statement; News Brief on the Executive Board Discussion; and Statement by the Authorities of Turkey. (IMF Staff Country Reports; Country Report, 2002)
This paper evaluates Turkey's Second Review Under the Stand-By Arrangement (SBA). Since the completion of the Article IV Consultation and the first review in April 2002, macroeconomic policies have remained in line with the program. All quantitative performance criteria for end-March and end-April have been met. In light of continued strong program implementation, the IMF staff recommends the completion of the second review. Strict implementation has already produced tangible economic gains, and the authorities are determined to stay the course.